An IMRT/VMAT Technique for Nonsmall Cell Lung Cancer. (11th October 2015) - Zhao, Nan; Yang, Ruijie; Wang, Junjie; Zhang, Xile; Li, Jinna
Abstract : The study is to investigate a Hybrid IMRT/VMAT technique which combines intensity modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT) for the treatment of nonsmall cell lung cancer (NSCLC). Two partial arcs VMAT, 5-field IMRT, and hybrid plans were created for 15 patients with NSCLC. The hybrid plans were combination of 2 partial arcs VMAT and 5-field IMRT. The dose distribution of planning target volume (PTV) and organs at risk (OARs) for hybrid technique was compared with IMRT and VMAT. The monitor units (MUs) and treatment delivery time were also evaluated. Hybrid technique significantly improved the target conformity and homogeneity compared with IMRT and VMAT. The mean delivery time of IMRT, VMAT, and hybrid plans was 280 s, 114 s, and 327 s, respectively. The mean MUs needed for IMRT, VMAT, and hybrid plans were 933, 512, and 737, respectively. Hybrid technique reduced V 5, V 10, V 30, and MLD of normal lung compared with VMAT and spared the OARs better with fewer MUs with the cost of a little higher V 5, V 10, and mean lung dose (MLD) of normal lung compared with IMRT. Hybrid IMRT/VMAT can be a viable radiotherapy technique with better plan quality.